Organic fertilizer doses for top-dressing fertilization in jambu (Acmella oleracea [(L.) R. K. Jansen]) production - Nepomuceno Alves, Thatiane; Cardoso, Antonio Ismael Inácio; Nordi, Nicholas Taborda; Carvalho, Joseantonio Ribeiro de; Oliveira, Marcelo Munhoz Venâncio de; Luis, Débora Cristina Mastroleo; Lima de Sousa, Renan (Comunicata Scientiae, 2023)
Due to the lack of specific fertilization recommendations for jambu cultivation, producers commonly use fertilizers recommended for other vegetables. This study aimed to evaluate the effect of different doses of organic fertilizers, namely hoof and horn powder and castor bean cake, on jambu plant production under an organic system. The experiments were conducted at the Experimental Farm of São Manuel, SP, belonging to the School of Agriculture (FCA) – UNESP, and at the “Estância Três Nascentes” site, located in Botucatu, SP, Brazil. Twelve treatments were evaluated, in a 2 x 6 factorial design, consisting of two organic fertilizers (castor bean cake (CBC) and hoof and horn powder (HHP)) x 6 top dressing N doses (50, 75, 100, 125, 150, and 0 (control without these fertilizers)). The experimental design was a randomized block with four replications. Plant height (PH), number of inflorescences (NI), the fresh weight of inflorescence (FWI), the fresh weight of vegetative parts (FWVP), and the total fresh weight (TFW) were evaluated at each location. Linear increases were observed in all characteristics in both locations as the fertilizer doses increased. Comparing the highest dose (150 kg ha-1 of N) with the control, increases of 109%, 251%, 218%, 283%, and 227% were obtained at the farm in São Manuel, and 69%, 79%, 111%, 276%, and 118% in Botucatu, for PH, NI, FWVP, FWI, and TFW, respectively. When comparing the two fertilizers, HHP presented better results than CBC for most characteristics in both areas.